Influence of the use of calcium carbonate in the fertilization of Brachiaria decumbens and Brachiaria dictyoneura (Revista Sistemas de Producción Agroecológicos, 2018)
This experiment was carried out in a humid warm climate region with rainfall between 2700 and 3000 mm/year, with acid and low fertility soils, whose objective was to evaluate the application of calcium carbonate (CaCO3) and fertilizers in two types of grasses to establish interactions between soil chemical properties and forage production. The calculation of the amount of lime to be applied (total dose (TD)) was made based on the percentage of tolerable aluminum, for which the treatments were: E1 = 0 ton/ha (control), E2 = 0.74 ton/ha (1/3 of TD), E3 = 1.49 ton/ha (2/3 of TD) and E4 = 2.24 ton/ha (3/3 of TD) of CaCO3 applied in all treatments after the recovery of the pasture at 45 days. The design was randomized complete blocks with factorial arrangement by type of grass (Brachiaria decumbens and Brachiaria dictyoneura), applied dose of lime (4 amendments) and three components of fertilization (N, P, and K), with three repetitions for a total of 72 experimental units (2x4x3x3), each one of 16 m2, factors that were related to organic matter (OM), phosphorus (P), pH, aluminum (Al), calcium (Ca), magnesium (Mg), potassium (K) and sodium (Na). The variables analyzed were: green forage production (FV) and dry matter (DM). The statistical analysis was performed using ANOVA with 95% significance, and comparison of means with the Tukey test. The Al exchangeable in B. decumbens increased as the liming dose was increased, because in E3 and E4 it was greater than 2.2 cmolc/kg of soil; while with B. dictyoneura the dose of lime 1/3 of the total decreased it being less than 1.98, although both values remained high in the soil, indicating that the doses applied did not manage to reduce the excess of Al, being different from each other (P
Keywords: grass; acid soils; biomass production; pastures; livestock